Direct photocatalytic fluorination of benzylic C–H bonds with N-fluorobenzenesulfonimide1. Issue 59 (28th July 2015) - Nodwell, Matthew B.; Bagai, Abhimanyu; Halperin, Shira D.; Martin, Rainer E.; Knust, Henner; Britton, Robert
<x xml:space="preserve">Abstract</x> Two complimentary strategies for the direct fluorination of benzylic C–H bonds with NFSI are described using either AIBN-initiation or decatungstate photocatalysis.